EDUCATIONAL EQUITY AND LEARNING ENVIRONMENT OF SCHOOLS DIVISION OF ROXAS CITY - Besana, Michelle Ambion (IDEAS: Journal of Management & Technology, 2025)
Educational equity and learning environment are pressing issues among schools. Since the end of the COVID-19 pandemic, various programs monitoring efforts have been carried out to contribute significantly to the schools’ quality of services. One of those was this quantitative study which used a descriptive-correlational approach to investigate the level of educational equity and the extent of learning environment of junior high school students in Schools Division of Roxas City in the school year 2023-2024 as perceived by the teachers. After a comprehensive and critical review of data collected from two hundred and sixty-two (262) selected teacher-respondents, it was found that they perceived educational equity and learning environment as "very high". It revealed that there was no significant difference in the level of educational equity among junior high school students when respondents were grouped by age, sex, and educational attainment. Moreover, there was no significant difference in the extent of learning environment when teacher-respondents were grouped by age, sex, and educational attainment. The level of educational equity is significantly related to the extent of educational equity of the students. With these relevant results, it is recommended that schools should intensify and implement quality programs for all learners, provide equal learning opportunities, ensure free internet access, create learner's handbook, establish clubs and organizations, conduct trainings and seminars for teachers, and assign tasks and responsibilities relevant to teachers' age, gender, and expertise for them to be more productive and effective.